Tuning of graphene oxide composition by multiple oxidations for carbon dioxide storage and capture of toxic metals. Issue 6 (18th January 2017) - Nováček, Michal; Jankovský, Ondřej; Luxa, Jan; Sedmidubský, David; Pumera, Martin; Fila, Vlastimil; Lhotka, Miloslav; Klímová, Kateřina; Matějková, Stanislava; Sofer, Zdeněk
Abstract : The chemical composition and properties of graphene oxide can be controlled by multiple oxidations. Abstract : Graphene oxide (GO) is a material used as a precursor for the synthesis of graphene and its derivatives. Chemical properties of graphene are strongly influenced by the chemical composition of the original GO. In this paper we would like to show that the amount as well as the type of functional groups can be significantly increased and controlled by multiple oxidations of GO. For this purpose we performed multiple oxidations using two chlorate methods (Staudenmaier and Hofmann) and a permanganate method (Hummers). The results show a possibility of tuning the composition of GO functionalities by multiple oxidations. The obtained results also show that the second and third subsequent reoxidation reactions significantly increase the amount of oxygen containing groups in GO, mainly carboxylic groups. The multiple oxidation of graphene oxide led to a significant increase of carbon storage capacity. The high concentration of oxygen functionalities led to an increase of sorption capacity by more than one order of magnitude.